2002
DOI: 10.1046/j.1444-2906.2002.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen budget of polychaete Perinereis nuntia vallata fed on the feces of Japanese flounder

Abstract: The nitrogen budget of polychaete Perinereis nuntia vallata fed on Japanese flounder feces was estimated at 20°C. Worms of 0.2–0.6 g body weight ingested 4.9–25.7 mg/individual per day of flounder feces and excreted 1.2–5.5 mg/individual per day (dry weight) of fecal pellets corresponding to 12.2–44.1% (mean 22.4%) of fed flounder feces. Mean ammonia excretion rate of the worms fed the feces was 0.1 mg/individual per day. Based on the ingestion and excretion data and nitrogen content of flounder feces, worm fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 11 publications
4
41
2
Order By: Relevance
“…Different polychaete was used to reuse the aquaculture solid waste [11,12]. In this experiment, P.aibuhitensis not only acted well (the worms average Days Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different polychaete was used to reuse the aquaculture solid waste [11,12]. In this experiment, P.aibuhitensis not only acted well (the worms average Days Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(8)(9)(10)(11) show change in the water chemistry parameters in each group. It could be seen from Figures 7-10 that the change in Total Nitrogen (TN) was similar in each group, which increased and decreased smoothly throughout the experiment.…”
Section: The Change In Water Chemistry Parameters In Each Groupmentioning
confidence: 99%
“…However, the activities of the glycolytic pyruvate reductase enzyme and tauropine dehydrogenase of H. iris cultured in the high wave area increased significantly, whereas the glycogen content decreased, relative to abalones in the steady water flow area (Wells et al, 1998). Nitrogen (N) and phosphorous (P) are important elements in the material cycle in aquaculture systems, and any changes in their content and ratio will affect the distribution and accumulation of nutrient salts in the water as well as the flow and conversion of energy in the system (Garber & Hartman, 1985;Honda & Kikuchi, 2002;Lijklema, 1986). To date, the effects of flow velocity on growth, food intake and metabolism of H. discus hannai in a closed recirculating aquaculture system have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…They can also ingest and assimilate fecal waste from aquaculture farms. One study found that the polychaete Perinereis nuntia vallata converted approximately 50% of the nitrogen ingested from Japanese flounder (Paralichthys olivaceus) wastewater into body tissue [164]. Another study involving two species of intertidal polychaetes (Perinereis helleri & Perinereis nuntia) cultured in sand-beds to remediate wastewater from a prawn farm revealed that the polychaete filtration process significantly reduced chlorophyll a and suspended solids [165].…”
Section: Integrated Multi-trophic Aquaculture (Offshore and On-land)mentioning
confidence: 99%